(untitled) (Communication & Society, 2013)
Visual images in news photographs guide individuals’ understandings of people, places and events, especially when news audiences are unable to personally experience those represented images. When 41 Time newsmagazine covers from the first five years of the U.S.-led war on Iraq are considered through a framing analysis, four frames surface: The Sanitized War, Against the Powers-That-Be; The American Soldier in a Time of War; and The "Other" of the War, or "Us versus Them." These findings highlight the power of media messages to frame identity ideologies and stress the importance of complementing quantitative studies with qualitative approaches.